2009
DOI: 10.2754/avb200978010107
|View full text |Cite
|
Sign up to set email alerts
|

Body Size and Behaviour Traits of Dogs in Czech Households

Abstract: The objective of this study was to analyse the effect of body size of dogs on their coexistence with humans in Czech households. For this purpose we used questionnaire data on 246 dogs indicating the breed. The dogs were divided into five body size groups, i.e. toy (T, up to 5 kg body mass, n = 32), small (S, 5 -10 kg body mass, n = 52), medium size (M, 10 -17 kg body mass, n = 39), large (L, 17 -33 kg body mass, n = 70), giant (G, over 33 kg body mass, n = 53). The largest dogs surpassed the body mass of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Consequently, people might better tolerate aggression in smaller dogs and thus the selection pressure towards them might have been weaker (Duffy et al 2008). It has been shown that the size of the dog impacts the way it interacts with its owner (Kobelt et al 2003;Baranyiova et al 2009). Larger dogs are more likely to be trained and this training is more likely to be done by professionals (Kobelt et al 2003;Baranyiova et al 2009).…”
Section: Association Between Aggression and Other Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, people might better tolerate aggression in smaller dogs and thus the selection pressure towards them might have been weaker (Duffy et al 2008). It has been shown that the size of the dog impacts the way it interacts with its owner (Kobelt et al 2003;Baranyiova et al 2009). Larger dogs are more likely to be trained and this training is more likely to be done by professionals (Kobelt et al 2003;Baranyiova et al 2009).…”
Section: Association Between Aggression and Other Factorsmentioning
confidence: 99%
“…It has been shown that the size of the dog impacts the way it interacts with its owner (Kobelt et al 2003;Baranyiova et al 2009). Larger dogs are more likely to be trained and this training is more likely to be done by professionals (Kobelt et al 2003;Baranyiova et al 2009). Owners of small dogs engage less frequently in training activities (Baranyiova et al 2009) and, moreover, are less consistent overall (Arhant et al 2010).…”
Section: Association Between Aggression and Other Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, only a fraction of small dogs obtain any kind of training and their exercise is limited as well (Baranyiová et al , 2009). Such dogs may be predisposed to biting; in small dogs fear aggression may lead to biting.…”
Section: Discussionmentioning
confidence: 99%